ANALISIS SPASIAL TINGKAT BAHAYA LONGSORLAHAN DI KECAMATAN KEMALANG KABUPATEN KLATEN - Kuswaji Dwi Priyono; Restu Dagi Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Landslide was the movement of soil or rock down the slope through the sliding plane. Landslide is one form of masswasting that often occurs in research area Kemalang Sub District, Klaten District. Purpose of the research was : (1) analyze the level of landslide hazard in Kemalang Sub District, Klaten District, and (2) determine distribution of landslide in Kemalang Sub District, Klaten District. The parameters that being used were slope, rainfall, landuse, soil depth, rock weathering, soil structure and soil texture. The method that being used are weighting and scoring. Analysis spatial used quantitative tiered weighted approach.The giving of weight values based on the level of parameters that influence landslide. The result of the research was landslide hazard classification in Kemalang Sub District consist of three class, namely medium, high and very high. The distribution of landslide hazard include :(1) Keputran Village, Kemalang, Dompol, Tangkil, Bumiharjo, Bawukan, Talun, part of Panggang Village, Kendalsari, Tlogowatu and a small areain south side of Sidorejo Village with landslide hazard is medium which has area 29,89 km², (2) some area in Balerante Village, Sidorejo andnorthernmost Tegalmulyo that abut with top slope of Merapi Mountain with very high landslide hazard and total area 11,365 km², and (3) some area in Balerante Village, Sidorejo, Tegalmulyo, Kendalsari, Tlogowatu, and Panggang with high landslide hazard and total area 16,174 km².Keyword: spasial analysis, landslide hazard, weighting approach